Hubungan Beberapa Faktor Internal Dan Eksternal Dengan Hipertensi Pada Pasien Usia 45-59 Tahun Di Puskesmas Tawangsari Kabupaten Mojokerto Pada Agustus 2021 - Suci Rahmawati Hidayatulloh; Enggar Dwi Panglipur; Adelia Friska Imas; I Putu Yogie Mahendra; Sugiharto Sugiharto (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2022)
Hypertension is influenced by internal and external factors. Internal risk factors such as: age, gender and family history While external risk factors are risk factors caused by unhealthy behavior of people with hypertension and can be changed such as: smoking, low fiber diet, excessive salt consumption, obesity, drinking alcohol, dyslipidemia and stress. Therefore, this study aims to analyze whether there is a relationship between several internal and external factors with hypertension in patients aged 45-59 years at the Tawangsari Health Center, Mojokerto Regency in August 2021. Where the independent variables in this study were gender, family history, smoking and obesity while the dependent variable is hypertension. The design in this study is cross sectional and the population is all elderly who seek treatment at the Tawangsari Health Center, Mojokerto Regency in August 2021 as many as 44 elderly with a total sample of 40 patients. The data from the study were then processed using the Chi-square statistical test. Based on the results of the study, it was found that family history (genetic), smoking and obesity had a significant relationship with the incidence of hypertension at the age of 45-59 years. While the gender factor is known to have no relationship with the incidence of hypertension at the age of 45-59 years at the Tawangsari Health Center, Mojokerto Regency